National Survey of Hospital Medication Safety Practice during Mass Gathering (Hajj-2016) in Makka, Saudi Arabia: Medication Administration - Alomi, Yousef Ahmed; Khayat, Nezar Adnan Yahya; Baljoon, Mustafa Jamil; Bamagaus, Yasir Abdulraheem; Jumah, Hani Mohammed Ali (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of hospital medication safety practice during mass gathering (Hajj -2016) in Makkah, Saudi Arabia: Medication Administration, the finding of ISMP (2011) self-assessment of medication safety at the hospital. Methods: It is 15 days cross sectional national survey of hospital medication safety at Makkah region. The survey modified from Institution of Safe Medication Practice (ISMP) self-assessment of hospital medication safety. It consisted of a demographic section and ten domains with 270 questions. The ten areas included patient information, drug information, communication of medication orders, drug preparation, medication distribution, medication devices, work environment, staff competency, patient education, quality process with risk management domain. The 5-points Likert response scale system used. The survey distributed to sixteen directors of hospital pharmacy during mass gathering Hajj-2016. The medications safety officer at Makkah region distributed the questionnaire and made a follow-up on a daily basis used physical visiting and through the telephone call. Results: The survey distributed to sixteen hospitals, the response rate, was eleven hospitals (68.75%). The total score of all ISMP-self assessment of medication safety was 3.39 +/-0.51 (67.68 %) with CI (3.2-3.6) P< 0.05. The medication administration included two domains; drug standardization, storage, and distribution with scores 3.54 (71.8%), Medication devices acquisition, Use, and monitoring with scores 2.97 (59.4%). The highest score will all section was Antidotes for medications with guidelines use readily available 4.8 (96%). The lowest score was all electronic infusion pump full functionality to intercept and prevent wrong dose/wrong infusion rate errors 2.33 (46.6%). Conclusion: The standardized medication process during administration including ready-made preparations, fixed drug concentration, and standardized medication devices required during mass gathering Hajj period. The annual survey of medication administration safety with practical tools is potential to prevent any drug-related errors will create medication safety culture and avoid burden mistakes on health care system during mass gathering Hajj period in Makka, Saudi Arabia.
Keywords: Medication Safety; Hajj; Drug; Administration; Ministry of Health; Saudi Arabia